Does Malaysian Code of Corporate Governance ‘MCCG’ matter among family-controlled firms? - Lode, Nor Asma; Noh, I. M. (Akademia Baru, 2019)
The Securities Commission Malaysia issued the Corporate Governance Blueprint which is later transformed to Malaysian Code on Corporate Governance ‘MCCG’. Minority Shareholders Watchdog Group ‘MSWG’ is participating in the establishment of MCCG components as well as the measurement of best practice of corporate governance by using Corporate Governance’s index in 2009. This index which has two components of internal governance (i.e. disclosures on board of directors’ structure and directors’ remuneration) and external governance (i.e. disclosures on accountability and audit as well as communication with shareholders) could result to an effective monitoring and governance among family-controlled firms. Using MCCG index scores, this study examines the relationship between the components of corporate governance and performance among Malaysian family-controlled firms for the years 2010 and 2011. The regression analysis provide evidence that none of these components are significant except directors’ remuneration disclosures which are negatively related to family-controlled firms’ performance (i.e. ROA, Tobin Q and EVA). These findings indicate that low disclosures of directors’ remuneration are more likely to be related to high performance among family-controlled firms given that more investors may be attracted to invest in the family businesses with low directors’ remuneration than high directors’ remuneration. Hence, the regulators and policy makers may need to consider specific corporate governance code for family-controlled firms in order to lessen the dominance of agency problems.